Diversity of non-symbiotic nitrogen-fixing bacteria and their potential in andisols affected by the eruption of Mount Sinabung, North Sumatra, Indonesia - mariani sembiring; T. SABRINA (Society for Indonesian Biodiversity, 2021)
Abstract. Sembiribg M, Sabrina T. 2021. Diversity of non-symbiotic nitrogen-fixing bacteria and their potential in andisols affected by the eruption of Mount Sinabung, North Sumatra, Indonesia. Biodiversitas 22: 3539-3544. Nitrogen is the main macro-nutrient that is very important for plant growth. Nitrogen is absorbed by plants in the form of NO3-or NH4+ ions from the soil. The andisols affected by the eruption of Mount Sinabung alter the chemical, physical and biological characteristics of the soil. As a result, the population of beneficial microbes in the soil decreased, so soil fertility also decreased. The aim of this research is to determine the diversity of nitrogen-fixing microbes in andisol soil affected by the Mt. Sinabung eruption. The soil samples used in this research were collected from andisols affected by the eruption of Mount Sinabung. The isolation of non-symbiotic nitrogen-fixing bacteria was carried out using a nitrogen-free Jensen medium. The results showed that five non symbiotic N-fixing bacteria can increase the N content in andisols affected by Mount Sinabung eruption. Enterobacter cloacae can increase soil N by 111.76% as compared to without microbial application.